Blue Economy Concept in Extension Waste of Fish Baung Into Fish Oil in Sungai Paku Village Kampar Kiri, Kampar Regency, Riau Province - Ilza, Mirna; Ikhsan, Ikhsan; Buchori, Buchori (International Journal of Economic, Business & Applications, 2019)
Service to the public entitled "Guidance processing of fish waste baung into fish oil in Sei Paku Village, Kampar Kiri, Kampar District, Riau Province "has been carried out for 4 months in order to: 1) provide understanding and insight to the participants extension that baung fish waste can be processed into fish oil. 2) Giving briefing to the participants on the techniques of fish waste processing into fish oil. 3) To motivate participants to conduct business based processed fish waste products to supplement the family income. 4) Maintaining the quality and quantity of fish oil products produced in order to penetrate the wider market. 5) Provide new jobs. 6) Realize blue economy. Blue Economy is an economic concept that will be developed in Sei Paku to the challenging of environmentally destructive economic system, the damage caused by the presence of fish processing waste baung released into the environment. Interest extension with the motto of Blue Economy is no waste is wasted, meaning that all fishery products including waste can be utilized to improve the welfare of the community. Method of activities undertaken to achieve the goal of community service are lectures, discussions, consultations and practical demonstrations directly manufacture baung fish waste into fish oil. Counseling is done four stages starting with preparation for the month of August 2016, the implementation in September 2016, the establishment of a business group in October 2016, evaluation and monitoring in November 2016. As a result, at the end of public education can already take advantage of the technology is taught and business groups has been formed to start a business based on fish waste to increase the family income at the same time realizing the BlueEconomy